Anticipating the impact of natural disaster on foreign tourists through collaboration in the city of Pare-Pare - Rusdi, Muh. (Technium Sustainability, 2021)
The purpose of this research is to build a collaboration between the travel business and the relevant government and the people of the City of Parepare in dealing with disasters. In addition, the parties who are members of the collaboration group carry out the stages of the safety process for tourists affected by the disaster to facilitate the handling of accident victims in the field. in the City of Parepare. Then this study, using a descriptive qualitative approach, the data collection techniques used are interviews, literature study, observation and documentation. The results of this study indicate that it is necessary to establish cooperation carried out by travel business parties to related sectors in the form of collaboration and the need for a soup or guide book to be made as a way to facilitate and understand the duties of each member of the cooperation group. are required to be able to equip their employees by adding skills and training, especially those related to First Aid in Accidents (P3K) this is important for travel businesses and related agencies to avoid more serious accident victims for tourists.